Remnant hollowed out dead coral skeleton branches defer coral community recovery - Kathryn C. Scafidi; Kyle W. Fouke; Mayandi Sivaguru; Bruce W. Fouke; Peter J. Edmunds (PLoS ONE, 2026)
Through repeated impacts of ecosystem disturbances, most coral reefs have transitioned to a degraded state with low living coral cover. Until recently, the reefs of Moorea, French Polynesia, have provided an exception to this trend as their coral communities have recovered from sequential disturbances over the last 50 years. Early in 2019, the north shore fore reef at 10-m depth had ~ 75% live coral cover, but was decimated by bleaching to leave 17% coral cover by August 2020 and many kilometers of reef dominated by dead-in-place colonies of Pocillopora spp. By 2025, coral recovery had not begun because of the chronology of decay affecting dead Pocillopora skeletons. We combine ecological analyses of dead Pocillopora colonies with high-resolution microscopy of aragonite skeletal structure to better understand the fate of these dead branching corals. Bleaching in 2019 created a reef dominated by dead Pocillopora colonies that initially were resilient to breakage and removal. Dead corals were colonized by macroalgae, occupied by a unique assemblage of invertebrates, and deterred coral recruitment as evidenced by coral settlers on settlement tiles but not on dead skeletons. In 2022–2023, three years after Pocillopora colonies were killed, their remnant hollowed-out branches were first detected. High-resolution microscopy indicates hollowing occurred through bioerosion of dead branches that were scaffolded by encrusting taxa and entrapped sediments. Over 2011–2019, coral communities in Moorea rapidly recovered from devastation, but recovery from the 2019 bleaching has been deferred by the retention of dead corals on reef surfaces, creating the opportunity for erosion to further hollow out and weaken dead coral branches. This study shows how the synergy of well-studied disturbances can create ecological surprises that at best defer community recovery, but at worst portend a different outcome of major disturbance events, preventing recovery of the original coral community.